The effect of age on sprinting performance during acceleration in long jump athletes - Mironov A.O.; Gerasimov M.V.; Vinogradova O.P.; Spiridonov E.A. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to study the peculiarities of the influence of the age factor on the manifestation of speed and strength qualities in the run–up phase of long jumpers. Methods and structure of the study. The study involved 35 young athletes specializing in the long jump. The participants were divided into two age categories: the first group included athletes aged 15.5±0.6 years, and the second – 18.4±0.6 years. Using regression analysis methods, a measure of the influence (determination) of various factors on the result of the long jump was established. The indicators characterizing speed and strength qualities, flexibility, general and explosive strength, as well as the speed of sprinting were considered as predictors. Results and conclusions. Over the years, the importance of sprint speed for the successful long jump has increased, due to a complex of biological changes. Predicting the results of long jumps for athletes of different age groups becomes more accurate when using tests that measure the explosive strength of the muscles of the lower body.